Linking integrity with road pricing cause-and-effect model: A system dynamics simulation approach - Masriah, Mansur; Zetty Ain, Kamaruzzaman; Ahmad Afif, Ahmarofi; Cheng, Jack Kie; Hamirahanim, Abdul Rahman; K. A., Masri; Nadirah, Abdul Rahim; Sarifah Radiah, ShariffS (Penerbit UMP, 2022)
With Malaysia's rapid urbanisation and continuous improvement of living standards, vehicle ownership and trip volume continue to grow. Increases in motor traffic in large cities and their environs result in a number of social, environmental, and economic issues, which are frequently attributable to the widespread use of automobiles as the primary mode of urban transportation. This exacerbates traffic congestion on the country's highways, particularly in urban areas such as Kuala Lumpur. This traffic congestion poses an ongoing threat to the sustainability of transport development. Thus, by using the system dynamics, this study establishes a cause-and-effect relationship regarding the implementation of road pricing as a tool for reducing congestion and a stepping stone for enhancing sustainability. Road pricing is a direct charge assessed to drivers who use the road network with the goal of reducing the number of private vehicles on the road during peak hours. The developed Causal Loop Diagram (CLD) composed of five subsystems: road congestion, road attractiveness, new road construction, public transportation, and road pricing. The road congestion, new road construction, and road pricing all encounter mutual reinforcement as a result of a variety of negative polarities. As a result, authorities should place a greater emphasis on these loopholes, as they will inevitably result in unexpected changes. Additionally, by incorporating holistic perspectives from previous works and experts in the field, CLD can aid in identifying the primary factors underlying the problem being studied. In future work, the developed CLD should be extended to the next stage of the SD model, dubbed stock-flow-diagram (SFD).